CONFLICT OF MOTIVATION OF PROFESSIONAL ACTIVITY MEDSESTER WITH DIFFERENT LEVEL OF EMOTIONAL HEALTH - Pavlyuk, Tetiana Nikolaevna (Psychological Prospects Journal, 2013)
The article presents the results of an empirical study of the peculiarities of the motivation of the professional activity of nurses with different levels of emotional burnout. The specificity of the conflicts of conscious and unconscious professional motivation is revealed.